(untitled) - Larson, Mildred L. (Lanham, Md., 1998)
This textbook has been designed to emphasize the differences between languages and how this affects the translation of a text from one language into another. It is based upon the principle that the translator must first know the meaning of the source text before he can translate it into the receptor language. Meaning is presented as a structure which stands behind any text. Meaning-based, rather than form-based, translation is the goal of the textbook.
Keywords: Biên dịch và phiên dịch,Translating and interpreting